2020
DOI: 10.3390/v12020142
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Molecular Cluster Detection and Evaluation of Cluster Investigation Criteria Using Machine Learning Methods and Statewide Surveillance Data in Washington State

Abstract: Molecular cluster detection can be used to interrupt HIV transmission but is dependent on identifying clusters where transmission is likely. We characterized molecular cluster detection in Washington State, evaluated the current cluster investigation criteria, and developed a criterion using machine learning. The population living with HIV (PLWH) in Washington State, those with an analyzable genotype sequences, and those in clusters were described across demographic characteristics from 2015 to2018. The relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…First, our priority cluster definition for this analysis used a threshold of five diagnoses in the preceding 12 months. However, clusters with as few as three diagnoses in the preceding 12 months have equally high growth and transmission rates [ 3 , 16 ]. The CDC currently applies the lower threshold to areas with lower numbers of HIV diagnoses, and some health departments in higher burden areas that have capacity to respond earlier also use lower thresholds.…”
Section: Discussionmentioning
confidence: 99%
“…First, our priority cluster definition for this analysis used a threshold of five diagnoses in the preceding 12 months. However, clusters with as few as three diagnoses in the preceding 12 months have equally high growth and transmission rates [ 3 , 16 ]. The CDC currently applies the lower threshold to areas with lower numbers of HIV diagnoses, and some health departments in higher burden areas that have capacity to respond earlier also use lower thresholds.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings show “short-lived” small cluster lineages epidemiologically resemble solitary transmissions while being distinct from “super-spreader” larger cluster variants. Stable large cluster lineages have been recently shown to fuel the Rhode Island, North Carolina, and New York statewide epidemics and may contribute to more transmissible drug-resistant epidemics [ 16 , 27 , 33 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This shorter genetic distance is estimated to evolve over approximately 2–3 years [ 44 ]. Our findings found that this lower cut-off may not always assist in forecasting cluster growth [ 26 , 27 , 33 ]. Analyses at genetic distances of 1.5% and 2.5% thresholds assisted in distinguishing patterns of spread of large cluster networks implicated in the Quebec epidemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more stringent TN93 threshold of 0.5% is often used to identify the most recent and rapid clusters of HIV-1 transmission ( Fig 2B). Threshold determinations are often informed by cluster size and growth rate criteria (Erly, et al, 2020;France and Oster, 2020;Oster, et al, 2018). MicrobeTrace offers the ability to filter by genetic distance and cluster size thresholds in the same 'Global Settings' menu.…”
Section: Genetic Distance Networkmentioning
confidence: 99%